'Forced to Friendship'? Russian (Mis‐)Understandings of Soft Power and the Implications for Audience Attraction in Ukraine. (14th July 2015) - Hudson, Victoria
Abstract : This article argues that for all its efforts to implement soft power techniques, the Kremlin still fails to grasp the subtle, voluntaristic essence of soft power. This is reflected in a style of public interaction that has practical implications for how Russian soft power overtures are received by the audience. This is demonstrated through the findings of mixed‐method empirical research from four Ukrainian regions. Thus, while surveys show that the worldview promoted by Russian public diplomacy resonates to some extent, insights from focus groups indicate that potential attraction is nevertheless limited by Russia's 'hard' and obtrusive approach to cultural influence.